Prognostic role of platelet-to-lymphocyte ratio in patients with rectal cancer undergoing resection: a systematic review and meta-analysis - Ma, Lijuan; Yang, Fei; Guo, Wentao; Tang, Shufang; Ling, Yarui (Frontiers in Oncology, 2024)
BackgroundInflammation plays a pivotal role in tumor growth, with the platelet-to-lymphocyte ratio (PLR) emerging as a promising serum biomarker for prognostic assessment in patients with cancer. However, its specific role in rectal cancer remains controversial.MethodsA comprehensive literature review encompassing PubMed, EMBASE, and the Cochrane Library, spanning from their inception to March 2024, was conducted. The systematic review and meta-analysis strictly adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines (PRISMA). Quality assessment was conducted using the Newcastle–Ottawa scale (NOS). This study aimed to assess the available literature on the association of PLR with both overall survival (OS) and disease-free survival (DFS) in patients with rectal cancer undergoing resection.ResultsTwenty-three observational studies, encompassing 7577 patients, were included in the analysis. These comprised 20 retrospective and 3 prospective cohort studies, with NOS scores ranging from 5 to 8. A significant association was found between high PLR and worse OS (hazard ratio [HR] 1.00; 95% confidence interval [CI] 1.00–1.01; P = 0.01). Conversely, no significant association was observed between PLR and DFS (HR 1.14; 95% CI 0.98–1.32; P = 0.09).ConclusionsPLR serves as an independent clinical predictor of OS in patients with rectal cancer treated with curative surgery, but not of DFS. This easily accessible biomarker appears to be an optimal prognostic index and may aid clinicians in predicting the prognosis of rectal cancer, facilitating the development of individualized treatment strategies.